1977
DOI: 10.1128/aac.12.3.395
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Action of Morganocin 174

Abstract: Morganocin 174-induced lethality was characterized by one-hit kinetics. Although it induced simultaneous inhibition of deoxyribonucleic acid, ribonucleic acid, and protein syntheses, the most striking effect of morganocin was a rapid reduction of intracellular adenosine 5'-triphosphate to less than 10% of the initial values within 2 min of addition. Accumulation of thymidine, uridine, glutamine, and proline was also inhibited. A gradual efflux of K+ was observed, but the lethal effects of morganocin 174 could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1978
1978
1979
1979

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…120 110 E Ten minutes after the addition of bacteriocin, As with many other bacteriocins, the killing of the Bacteroides cells follows single-hit kinetics, and the interaction of a single molecule of bacteriocin with a target cell occurs in two stages. Pretreatment with 2,4-dinitrophenol inhibits uptake of the bacteriocin, and because it is a known uncoupler of oxidative phosphorylation and dissipator of membrane energy it is suggested that 2,4-dinitrophenol prevents the transmission of the bacteriocin by interfering with the energy supply (14,29). However, a direct interaction of 2,4-dinitrophenol with some membrane component essential for bacteriocin action cannot be ruled out (19).…”
Section: Resultsmentioning
confidence: 99%
“…120 110 E Ten minutes after the addition of bacteriocin, As with many other bacteriocins, the killing of the Bacteroides cells follows single-hit kinetics, and the interaction of a single molecule of bacteriocin with a target cell occurs in two stages. Pretreatment with 2,4-dinitrophenol inhibits uptake of the bacteriocin, and because it is a known uncoupler of oxidative phosphorylation and dissipator of membrane energy it is suggested that 2,4-dinitrophenol prevents the transmission of the bacteriocin by interfering with the energy supply (14,29). However, a direct interaction of 2,4-dinitrophenol with some membrane component essential for bacteriocin action cannot be ruled out (19).…”
Section: Resultsmentioning
confidence: 99%
“…This bacteriocin, morganocin 174, interferes with the energy metabolism of sensitive cells. Characteristics of this interference include inhibition of macromolecular synthesis and intracellular accumulation of glutamine and proline, efflux of K+, and rapid depletion of intracellular ATP (12). Although the genetic determinant of morganocin 174, plasmid Morl74, is nonconjugative, conjugal transfer may be mediated by a mobilizing plasmid, kanamycin re-"cleared" lysate was centrifuged to equilibrium in cesium chloride (CsCl)-ethidium bromide (EtBr).…”
mentioning
confidence: 99%